Pemberian Hibah Pemerintah Provinsi Bali Kepada Desa Pakraman - Ketut Gita Lestari; I Wayan Arthanaya; Luh Putu Suryani (Fakultas Hukum Universitas Warmadewa, 2019)
Provisions for granting grants are contained in the Law concerning Regional Government which states that grants and social assistance expenditures are budgeted in the APBD in accordance with regional financial capacity. To overcome confusion over Government funding recipient object in this case the Ministry of Interior issued a Regulation on the Amendment on Guidelines for Grants. Government P rovincial B ali quite cautious in giving grants to Pakraman. The government should be careful in interpreting whether Pakraman including bodies and agencies which are set in the Regulation. The formulation of the problem raised is 1. What are the conditions for awarding grants in Bali Province? 2. What is the procedure for awarding grants in Bali Province? The type of writing is Legal Normative approach to legislation and legal norms in force, t eknik collection started with an inventory by collecting and organizing legal materials into an information system and using description techniques by describing them first and then analyzing and then concluding. Government Authority Bali Province inside gift grant function for ngkatan meni service and welfare of the community, from the results observations of researchers regarding the process of implementing community grant programs in the city of Denpasar are in accordance with the provisions of the law, but there are still grants and social assistance that are not in accordance with the applicable provisions or requirements that have not been met . The mechanism for granting grants to the Bali Provincial Government is based on the Pergub Hibah and Bansos with apply the logic flow that giving grants to community organizations that are not registered in the ministry will support the existence and development of Balinese culture